REFORMULASI KETENTUAN PASAL40 AYAT 2 UNDANG-UNDANG NOMOR 5 TAHUN 1990TENTANG KONSERVASI SUMBER DAYA ALAM HAYATIDAN EKOSISTEMNYA TERHADAP PELAKU EKSPLOITASI HEWAN DALAM PERSPEKTIFHUKUM PIDANA INDONESIA - Rizki Pratama Kaloko; Erdianto Effendi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Exploitation of animals in recent times often occur in the territory of Indonesia both from the use to the destruction of these animals. In this case it is explained in Article 33 Paragraph (3) of the 1945 Constitution, which explains that